2017
DOI: 10.1007/s10815-017-0904-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreased live births among women of Middle Eastern/North African ethnicity compared to Caucasian women

Abstract: Middle Eastern/North African women have worse IVF outcomes with decreased live birth rates per blastocyst transfer and increased miscarriage rates compared to Caucasian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…However, the biologic or environmental factors underpinning these trends remain poorly understood. Previous studies have consistently reported higher rates of male factor infertility in the Arab or MENA population [8,9,17], with smoking, consanguinity, and family clustering being identified as putative risk factors [18,19]. Other studies have also reported that ethnic minorities may have a higher prevalence of women who are overweight and obese, which can be detrimental to oocyte yields and pregnancy rates [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the biologic or environmental factors underpinning these trends remain poorly understood. Previous studies have consistently reported higher rates of male factor infertility in the Arab or MENA population [8,9,17], with smoking, consanguinity, and family clustering being identified as putative risk factors [18,19]. Other studies have also reported that ethnic minorities may have a higher prevalence of women who are overweight and obese, which can be detrimental to oocyte yields and pregnancy rates [20].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a younger age and higher prevalence PCOS, MENA patients had lower oocyte yields; thus, the authors concluded that MENA patients likely had a more rapid decline in ovarian function when compared to Caucasian patients. In a more recent study, Salem et al [9] compared the outcomes of 190 MENA and 200 Caucasian patients undergoing their first IVF cycle. Like the study by Feichtinger et al [8], the authors found that MENA patients were younger and had a higher prevalence of male factor infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that ovarian reserve is, besides age, influenced by several factors including the sociocultural environment, habits and ethnicity. Previous publications have demonstrated, that Asian, African American, Hispanic, Indian American have lower live birth rates (LBR) and higher miscarriage rates after ART when compared to a reference population of white/Caucasian women (30)(31)(32)(33)(34)(35)(36)(37). Despite the fact that the Arabian culture is a pro-family society and families commonly have a higher number of children compared to couples in Western societies (38,39), there is a high prevalence of infertility in the MENA region (40) and very limited knowledge about ovarian reserve parameters and ART outcomes in the Arab population.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated in the Middle East region that the percentage of couples in which male factor is included as one of multiple factors attributed to the couples' difficulty to conceive is approximately 60-70% [6]. Interestingly, racial differences have been demonstrated in semen parameters of infertile men [7][8][9], and data from Qatar [10] revealed significantly lower semen quality parameters in infertile patients from the MENA region compared to non-MENA regions. In pro-natalist societies of the Middle East, an important part of manhood is the ability to father a child and therefore the inability to do so is generally considered to be a potentially emasculating condition [11].…”
mentioning
confidence: 99%